The Explanatory Role of Events in Causal and Temporal Reasoning in Medicine - Buekens, F.; Ceusters, W.; De Moor, G. (Methods of Information in Medicine, 1993)
The logic of time and the way we reason about time is intrinsically connected with the way we reason about causality. In this paper, we focus our attention on some of the less obvious ways in which reasoning about time and causality interact. It is explained why in temporal reasoning a firm distinction has to be made between the ontology, i. e., what happens, and the way we describe the ontology. Temporal events need to be redescribed in such a way that they causally explain why some of the events are followed by the others. While building a temporal/causal theory, certain events may be omitted, not because they do not play a causal role, but because they do not play an explanatory role. In doing so, it is possible to eliminate the distinction between theories representing time as dense, and theories that represent time as discrete.
Keywords: Temporal Reasoning; Causality; Explanation